Whole-genome resequencing in the sea louse Caligus rogercresseyi uncovers gene duplications and copy number variants associated with pesticide resistance - Núñez-Acuña, Gustavo; Sáez-Vera, Constanza; Valenzuela-Miranda, Diego; Valenzuela-Muñoz, Valentina; Gallardo-Escárate, Cristian (Frontiers in Marine Science, 2023)
The sea louse Caligus rogercresseyi is a marine ectoparasite that constitutes one of the major threats to the salmon farming industry, where the primary control strategy is the use of delousing drugs through immersion treatments. The emergence of pharmacological resistance in this copepodid species has previously been described using transcriptome data. However, the molecular mechanisms underlying chromosome rearrangements have not yet been explored. This study aimed to identify structural genomic variations and gene expression in C. rogercresseyi associated with pesticide sensitivity. In this study, genome resequencing was conducted using Oxford Nanopore Technology on lice strains with contrasting sensitivity to azamethiphos to detect genome duplications. Transcriptome profiling of putative gene duplications was performed by Illumina sequencing. Copy Number Variants (CNVs) were identified through comparative coverage, and collinear/tandem gene duplications over all the chromosomal regions by sequence homology. Duplications or CNVs in functional genes were primarily identified in transposable elements and genes related to the drug response, with differential expression values calculated by RNA-seq analyses of the same strains. Notably, differentially duplicated genes were found in coding regions related to cuticle proteins, suggesting that a putative resistance mechanism may be associated with cuticular structure formation and the proteins involved. Collectively, the results revealed that the intensive use of pesticides on sea lice populations increases the frequency of gene duplication, expanding the molecular elements involved in drug response. This study is the first to report an association between genome rearrangements and pharmacological resistance in sea lice populations.